Desarrollo de una aplicación móvil para estudiantes con dislexia para la asignatura de lengua y literatura - Velepucha Nagua, Martha Mariela; Rubio Pineda, Jose Fernando (Machala, 2023)
Based on an investigation, it was possible to identify the shortcomings or problems that students with dyslexia have within the teaching-learning process, therefore the construction of a mobile application developed in FlutterFlow was projected, for its proper implementation as a means or didactic strategy to enhance the content to provide feedback to students with dyslexia within the subject of language and literature. Based on direct observation, within a context we proceeded to a thorough analysis of special educational needs such as dyslexia, through the head of the Department of Student Counseling (DECE), we were able to determine a problem and notified the teacher in charge of the subject, to show the ideas to develop in the creation of a resource that is directed to students with dyslexia which would benefit as learning feedback through content focused on the subject. Based on the problems encountered, it was identified that there are students with dyslexia which affects their academic performance in the first year of high school. Therefore, the following question is posed: How to enhance the teaching-learning process through the development of a mobile application as a teaching strategy for students with dyslexia in the subject of language and literature in the first year of high school at the high school "El Progreso" of Cantón Pasaje? The research contextualizes the use of a mixed approach, that is to say, it is qualitative and quantitative for the adequate collection of informative data, in addition the research based on design will be used so that the contents are systematized, and the ADDIE model for the development of the prototype, In addition, in the data collection we opted for the use of measurement techniques and instruments, during experience I we used a survey directed to the teacher and in experience II of language and literature, a survey directed to the students about the implementation of the mobile app Dismarp in the classroom. During experience I we had the participation of the teacher in charge of the subject of language and literature of the first year of high school, who was shown the mobile app developed on the FlutterFlow platform and how the contents of the Teaching Unit Plan (PUD) is integrated to provide feedback for learning in students with dyslexia, while in experience II the Dismarp mobile app was applied within the mobile devices of the students who were interacting with the activities. Based on the research conducted, it was possible to show how the development and implementation of the mobile app Dismarp within the subject of language and literature generates a new way of learning and teaching in an autonomous way, allowing feedback on the contents and activities of the subject, adapting them for students who have problems with dyslexia, showing a new innovative approach that call the attention of each of the students of the first year of high school.
En base a una investigación se logró identificar las falencias o problemas que tienen los estudiantes con dislexia dentro del proceso de enseñanza-aprendizaje, por ello se proyectó la construcción de una aplicación móvil desarrollado en FlutterFlow, para su adecuada implementación como un medio o estrategia didáctica potenciando los contenidos para retroalimentar a los estudiantes con dislexia dentro de la asignatura de lengua y literatura. En base a la observación directa, dentro de un contexto se procedió a un analizó minucioso sobre las necesidades educativas especiales como lo es la dislexia, mediante el encargado del Departamento de Consejería Estudiantil (DECE), se logró determinar una problemática y se notificó al docente a cargo de la asignatura, para mostrar las ideas a desarrollar en la creación de un recurso que este direccionado a los estudiantes con dislexia lo cual beneficiaria como retroalimentador de aprendizaje mediante contenidos focalizados a la asignatura. En base a la problemática encontrada se identificó que existen estudiantes con dislexia lo cual afecta su rendimiento académico dentro del curso de primero de bachillerato, Por ende se plantea la siguiente pregunta: ¿Cómo potenciar el proceso de enseñanza-aprendizaje mediante el desarrollo de una aplicación móvil como estrategia didáctica en los estudiantes con Dislexia de la asignatura de lengua y literatura del primero de bachillerato del colegio de Bachillerato “El Progreso” del Cantón Pasaje? En la investigación se contextualiza la utilización de un enfoque mixto, es decir que es cualitativo y cuantitativo para la adecuada obtención de datos informativos, además se utilizara la investigación basada en diseño para que los contenidos se encuentren sistematizados, y el modelo ADDIE para el desarrollo del prototipo, además en la recopilación de datos se optó por la utilización de las técnicas e instrumentos de medida durante la experiencia I se ejecutó la utilización de encuesta dirigida el docente y en la experiencia II de lengua y literatura una encuesta dirigida a los estudiantes sobre la implementación de la app móvil Dismarp dentro de aula de clase. Durante la experiencia I se contó con la participación del docente encargado de la asignatura de lengua y literatura del primero de bachillerato, al cuales se le mostro la app móvil desarrollada en la plataforma FlutterFlow y como los contenidos del Plan de Unidad Didáctica (PUD) está integrado para retroalimentar el aprendizaje en los estudiantes con dislexia, mientras que en la experiencia II se aplicó la app móvil Dismarp dentro de los dispositivos móviles de los estudiantes los cuales iban interactuando con las actividades. En base a la investigación realizada se logró mostrar como el desarrollo y la implementación de la app móvil Dismarp dentro de la asignatura de lengua y literatura genera una nueva forma aprender y ensenar de manera autónoma permitiendo retroalimentar los contenidos y actividades de la asignatura adecuándolos para estudiantes que tienen problemas con la dislexia, mostrando un nuevo enfoque innovador que llaman a la atención de cada uno de los estudiantes del primero de bachillerato.
Keywords: APLICACION MOVIL; PROCESO DE ENSEÑANZA-APRENDIZAJE; TECNOLOGIA; ESTRATEGIAS EDUCATIVAS